Ecological generalism and behavioural innovation in birds: technical intelligence or the simple incorporation of new foods?. (9th July 2014) - Ducatez, Simon; Clavel, Joanne; Lefebvre, Louis; Quinn, John
Summary Generalist species are more successful than specialists in anthropogenically modified environments or in environments in which they have been introduced, but the nature of the link between generalism and establishment success is unclear. A higher feeding innovation rate has previously been reported in habitat generalist birds from North America. By allowing them to exploit new resources, this higher feeding innovation rate might explain the generalists' advantage. This result might be due to generalists being more likely to find new resources because they are exposed to more diverse environmental conditions. Alternatively, they might differ from specialists in other traits, in particular cognitive skills that might allow them to innovate more complex food searching and handling techniques. To test these hypotheses, we separated avian feeding innovations into a 'technical' (novel searching and handling behaviour) and a 'food type' (incorporation of a new food in a species' diet) category. Technical innovations, but not food type innovations, have previously been shown to correlate with avian brain size, suggesting they reflect cognitive ability. We used a world‐wide data base of 2339 feeding innovations recorded in the literature, covering a total of 765 avian species and assessed the correlations between brain size and feeding innovation rates on one side and habitat and diet generalism on the other. Habitat generalism was positively related with food type innovation rate, but not technical innovation rate or brain size. This suggests that habitat generalist species are more likely to incorporate new food types in their diet because of higher chances to find new food resources in their environment, or of a higher opportunism, but not enhanced cognitive skills. In contrast, diet generalist species had higher food type and technical innovation rates, as well as larger brains, suggesting that cognitive skills might help species expand their diet breadth or that an increase in diet breadth might favour the evolution of enhanced cognitive abilities. Our results provide new insights into the nature of the generalists' advantage in the face of environmental changes, and suggest that dietary and habitat generalism are different, but convergent, routes to feeding flexibility and adaptation to changed environments.